Composite diaphragm and battery

By using metal organic frame material and electrolyte gel in the battery separator, the problem of transition metal dissolution in the battery is solved, real-time removal of water and acidic impurities in the electrolyte is achieved, and the life and safety of the battery are improved.

CN119852645APending Publication Date: 2025-04-18WUXI NES ADVANCED MATERIALS & TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311301768.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-09
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively inhibit the dissolution of transition metals in high-nickel ternary material batteries, and traditional acid-removing and water removal agents cannot remove water and acidic impurities in real time during the battery charging and discharging process.

Method used

A composite separator is prepared by mixing metal organic frame material and electrolyte gel in a ratio of 5:5 to 9:1. By coating on the base film and heating, drying and curing, a metal organic frame material layer with a pore size range of 0.48-0.9 nm is formed.

Benefits of technology

The composite separator can effectively and in real time remove trace amounts of water and Lewis acid impurities in the electrolyte, protect high-nickel positive electrode materials, inhibit transition metal dissolution, reduce ionic crosstalk, and improve battery life and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852645A_ABST
    Figure CN119852645A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a composite diaphragm and a battery, and the composite diaphragm is prepared by the following method: mixing a metal organic framework material and electrolyte gel according to a mass ratio of 5: 5-9: 1 to prepare slurry, the aperture range of the metal organic framework material being 0.48-0.9 nm; and coating a base membrane with the slurry, and carrying out heating, drying and curing treatment to obtain the composite diaphragm. According to the composite diaphragm, on one hand, dissolution of transition metal can be inhibited, the problem of ion crosstalk can be reduced, the service life of the battery can be prolonged, the safety of the battery can be improved, on the other hand, the overpotential of the lithium metal battery can be reduced, and growth of lithium dendrites can be effectively inhibited. Furthermore, according to the composite diaphragm, a traditional commercial diaphragm can be used as a substrate, a metal organic framework material is directly coated to prepare the composite battery diaphragm, the method is simple and feasible, and the method can be directly used for industrial large-scale production of novel composite diaphragms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present invention relate to the field of battery technology, and in particular to a composite diaphragm and a battery. Background Art

[0002] High nickel ternary materials (LiNi x Co y Mn 1-x-y O 2 NCM) is widely used as anode material for lithium-ion batteries because of its high reversible capacity, high working voltage and abundant reserves. In the battery system, due to the limitation of production process technology, the trace water (<20ppm) in the electrolyte cannot be completely removed. The commonly used commercial electrolyte LiPF 6 It is very easy to react with trace water in the electrolyte to produce a series of Lewis acid impurities. Lithium ion conducting salts are hydrolyzed to produce HF and PF 5 ,POF 3 ,HPO 2 F 2 ,H 2 PO 3 Lewis acid impurities such as F and trace water impurities, among which acidic impurities such as HF will destroy the positive electrode-electrolyte interface film (SEI film), corrode the NCM ternary positive electrode material, cause particle breakage, transition metal (Ni, Co, Mn) dissolution and other hazards.

[0003] During the production and preparation of lithium batteries, lithium ion conductive salts easily absorb water, and the electrolyte storage environment and battery assembly environment have a significant impact on the water content in the battery electrolyte. Traditional acid and water removal agents can only remove water from the electrolyte before battery assembly, but cannot remove water and other acidic impurities generated during the battery charging and discharging process. Due to price and actual effect limitations, traditional acid and water removal agents cannot be used on a large scale.

[0004] Therefore, it is urgent to develop a real-time method for removing water and acid from the electrolyte to inhibit the dissolution of transition metals. Summary of the invention

[0005] The technical problem solved by the embodiments of the present invention is how to suppress the dissolution of transition metals in the ternary positive electrode.

[0006] In order to solve the above problems, an embodiment of the present invention provides a composite diaphragm, which is prepared by the following method:

[0007] (1) mixing a metal organic framework material and an electrolyte gel in a mass ratio of 5:5 to 9:1 to prepare a slurry, wherein the pore size range of the metal organic framework material is 0.48-0.9 nm;

[0008] (2) The slurry is coated on a base film, and subjected to a heating, drying and curing treatment to obtain the composite diaphragm.

[0009] Optionally, the heating, drying and curing treatment includes: drying in a forced air oven at 50-90° C., and then transferring to a vacuum oven and baking at 50-120° C. for more than 12 hours.

[0010] Optionally, the coating method includes blade coating, gravure roller coating, dip coating, narrow coating or spray coating.

[0011] Optionally, the slurry coating thickness ranges from 10 to 75 μm.

[0012] An embodiment of the present invention also provides a composite diaphragm, including a base membrane and a metal organic framework material layer, wherein the metal organic framework material layer is attached to at least one side surface of the base membrane, the metal organic framework material layer contains a metal organic framework material, and the pore size range of the metal organic framework material is 0.48-0.9nm.

[0013] Optionally, the metal organic framework material layer further includes an electrolyte gel, the electrolyte gel includes at least one of PVDF or PVDF-HFP, and the weight ratio of the metal organic framework material to the electrolyte gel is 5:5 to 9:1.

[0014] Optionally, the specific surface area of ​​the metal organic framework material ranges from 700 to 1300 m 2 / g.

[0015] Optionally, the metal organic framework material is selected from at least one of MOF-801, MOF-303, and MOF-74.

[0016] Optionally, the material of the base film is selected from at least one of polyolefin, glass fiber, and polyimide.

[0017] Optionally, the diaphragm has a thickness of 35 μm to 100 μm.

[0018] An embodiment of the present invention further provides a battery, comprising the aforementioned composite diaphragm.

[0019] The embodiments of the present invention have the following effects:

[0020] (1) This technical solution can use traditional commercial membranes as substrates to directly coat metal-organic framework materials to prepare composite membranes. The method is simple and feasible and can be directly used for industrial large-scale production of new composite membranes.

[0021] (2) The composite diaphragm can effectively and in real time remove the trace water remaining in the electrolyte and the water and Lewis acid impurities (HF, PF 5 ,POF 3 ,HPO 2 F 2,H 2 PO 3 F), protect high nickel cathode materials from corrosion, inhibit transition metal dissolution, reduce ion crosstalk problems, and improve battery life and safety.

[0022] (3) The composite separator can reduce the overpotential of lithium metal batteries and effectively inhibit the growth of lithium dendrites. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0024] Figure 1A This is a BET test graph of the specific surface area of ​​the metal organic framework material MOF-801 prepared in Example 1 of the present invention;

[0025] Figure 1B This is a pore size distribution test diagram of the metal organic framework material MOF-801 prepared in Example 1 of the present invention;

[0026] Figure 1C is a SEM image of the surface morphology of the composite diaphragm prepared in Example 1 of the present invention;

[0027] Figure 2 The adsorption energy & adsorption density calculation and adsorption energy calculation of MOF-801 prepared in Example 1 of the present invention for water and HF molecules;

[0028] Figure 3 1 is a graph showing the stability experiment and characterization test of MOF-801 prepared in Example 1 of the present invention, wherein FIG. a is an XRD spectrum, and FIG. b is a nitrogen adsorption test graph;

[0029] Figure 4 It is a comparison chart of the acid and water resistance test of NCM622||Li battery of Example 1 and Comparative Example 1;

[0030] Figure 5 is a comparison chart of the amount of transition metal dissolution in the NCM622||Li battery of Example 1 and Comparative Example 1;

[0031] Figure 6 This is a test diagram of the acid and water resistance electrochemical performance of lithium battery composite diaphragms with different MOF contents in Example 2 and Example 3;

[0032] Figure 7 It is a test diagram of the acid and water resistance electrochemical performance of lithium battery composite separators with different coating thicknesses in Example 4 and Example 5;

[0033] Figure 8 It is a comparison chart of the acid and water resistance test of NCM811||Li battery of Example 6 and Comparative Example 2;

[0034] Fig. 9 is a comparison chart of the amount of transition metal dissolution in the NCM811||Li battery of Example 6 and Comparative Example 2;

[0035] Fig.10 It is a comparison of the lithium symmetric battery cycle performance when using aqueous electrolyte in Example 1 and Comparative Example 1, as well as a SEM image of the lithium metal surface morphology. DETAILED DESCRIPTION

[0036] As can be seen from the background technology, the problem of transition metal dissolution in ternary batteries currently needs to be solved urgently.

[0037] To solve the above problems, an embodiment of the present invention provides a composite membrane, including a base membrane and a metal organic framework material layer, wherein the metal organic framework material layer is attached to at least one side surface of the base membrane, and the metal organic framework material layer contains a metal organic framework material.

[0038] The metal organic framework material is a porous structure. In a specific embodiment, the pore size range of the metal organic framework material is 0.48-0.9nm. On the one hand, the pore structure of suitable size is conducive to the enrichment of water molecules and hydrofluoric acid molecules, and improves the acid and water removal effect of the battery system. On the other hand, the rich pore structure of the composite diaphragm can be used as a carrier of the electrolyte. The physical screening of the pore size and the interaction of the pore chemical environment with the solvent molecules can achieve the purpose of achieving the desolvation configuration based on adsorption for the solvated molecules, thereby desolvating the solvated lithium ions and accelerating the lithium ion conduction, thereby reducing the overpotential of the lithium symmetric battery.

[0039] It should be noted that the metal organic framework material is attached to at least one side surface of the base film, which means that along the thickness direction of the base film, the metal organic framework material can be attached to one side surface or both sides of the base film.

[0040] It is easy to understand that although pure MOF diaphragm can solve the problem of removing water and acid and inhibiting the dissolution of transition metals, it is difficult to prepare a self-supporting MOF diaphragm due to the non-melting and non-dissolving characteristics of MOF. In order to ensure its stable circulation in the battery (sufficient mechanical strength), a composite method is usually used for preparation. The base film is used to carry the metal organic framework material to enhance the strength of the composite diaphragm. The material of the base film is selected from at least one of polyolefin, glass fiber or polyimide.

[0041] It should be noted that, as a diaphragm material, the metal organic framework material provided in the embodiment of the present application is not conductive, and the electrically neutral MOF has an electron shielding effect.

[0042] In a specific embodiment, the metal organic framework material layer also includes an electrolyte gel, the electrolyte gel includes at least one of PVDF or PVDF-HFP, the mass percentage of the metal organic framework material and the electrolyte gel is 5:5 to 9:1, and the electrolyte gel is used as a binder to improve the adhesion between the metal framework material and the base film. In a specific embodiment, the mass percentage of the metal organic framework material and the electrolyte gel is 3:2. In other embodiments, the mass percentage of the metal organic framework material and the electrolyte gel can also be 9:1, 2:1 or 5:5, etc., as long as the mass percentage of the metal organic framework material and the electrolyte gel is within the range of 5:5 to 9:1.

[0043] In order to reduce the corrosion of acidic substances on ternary cathode materials and the harm of transition metal dissolution, a metal organic framework material with a high specific surface area and polar groups in the pores can be selected. The metal organic framework material is selected from at least one of MOF-801, MOF-303, and MOF-74.

[0044] In a specific embodiment, the specific surface area of ​​the metal organic framework material is in the range of 700 to 1300 m 2 / g, high specific surface area is conducive to the full infiltration of electrolyte. Among them, the specific surface area is tested by BET method, and the test conditions are 80℃ degassing for 12h, N 2 Tested at 77K atmosphere.

[0045] The composite membrane provided in the embodiment of the present application is selected to have a high specific surface area (700-1300m2) with a moderate pore size (0.48-0.9nm) and a suitable pore environment (oxygen nucleophilic ligand). 2 / g) of MOF materials (MO-801, MOF-303, MOF-74, etc.), high specific surface area is conducive to the full infiltration of electrolyte, and the pore structure of suitable size is conducive to the enrichment of water molecules and hydrofluoric acid molecules, which improves the deacidification and dehydration effect of the battery system. The above advantages of MOF materials can continuously adsorb trace water in the electrolyte and Lewis acid impurities generated by the hydrolysis of lithium salts, reduce the corrosion of acidic substances on ternary cathode materials and the harm of transition metal dissolution, thereby achieving efficient and continuous water removal and inhibiting the harm of transition metal dissolution that accelerates battery aging.

[0046] In a specific embodiment, the composite membrane has a thickness of 35 μm to 100 μm, for example, 50 μm, 60 μm, 70 μm, or 80 μm.

[0047] It should be noted that the thickness of the composite diaphragm in this application refers to the sum of the base film thickness and the slurry coating thickness. The thickness of the slurry coating on the base film should not be too thick or too thin. If it is too thin, the water and acid absorption effect will be poor. If it is too thick, it will also affect the performance of the battery. In a specific embodiment, taking the base film thickness of 25μm as an example, the slurry coating thickness range is 10-75μm.

[0048] It should be noted that in aqueous electrolyte, LiPF 6 It is very easy to react with water to produce by-products (including acidic substances such as HF), which destroy the SEI film. In addition, the uneven accumulation of by-products on the surface of lithium metal will induce the nucleation and growth of lithium dendrites. After the composite diaphragm absorbs water and acid, it can inhibit the growth of dendrites.

[0049] This application is based on metal organic framework materials (MOF-801) and commercial PP membranes. The composite diaphragm prepared can continuously absorb trace water in the electrolyte and Lewis acid impurities generated by lithium salt hydrolysis, reduce the corrosion of acidic substances to ternary positive electrode materials and the harm of transition metal dissolution, thereby achieving efficient and continuous water removal and inhibiting transition metal dissolution. At the same time, the composite diaphragm can reduce the overpotential of lithium metal batteries, protect the SEI membrane from corrosion and damage by acidic substances, and prevent lithium dendrites from piercing the diaphragm, thereby improving battery safety.

[0050] In order to solve the above problems, an embodiment of the present invention provides a composite diaphragm, which is prepared by the following method:

[0051] Step S1, providing a metal organic framework material; mixing the metal organic framework material and an electrolyte gel in a mass ratio of 5:5 to 9:1 to prepare a slurry, wherein the pore size range of the metal organic framework material is 0.48-0.9 nm;

[0052] The metal organic framework material is selected from at least one of MOF-801, MOF-303, and MOF-74.

[0053] In a specific embodiment, the metal frame material is MOF-801 (Zr). MOF-801 (Zr) can be prepared by the following method: a certain mass of ZrOCl 2 8H 2O, fumaric acid, formic acid, and DMF were pre-reacted at 60-80°C and 500 r / min for 0.2-0.8 h; solvent thermal reaction was performed at 120-140°C and 500 r / min for 10-14 h; the mixture was washed alternately with a large amount of methanol and DMF three times, and centrifuged at 3000 r / min for 15 min; the product was placed in a watch glass, and vacuum dried and activated at 130°C for 12 h to obtain the metal organic framework material product MOF-801 (Zr). Of course, in other embodiments, commercial MOF-801 can also be purchased directly, as long as it can be ensured that MOF-801 meets the requirements of the pore size range and specific surface area range.

[0054] MOF-801 has a suitable pore environment (pore size of 0.48-0.9 nm, oxygen nucleophilic sites) and a specific surface area of ​​up to 840 m 2 / g. The above advantages of MOF-801 can continuously absorb trace water in the electrolyte and Lewis acid impurities generated by the hydrolysis of lithium salts, reduce the corrosion of acidic substances to ternary cathode materials and the harm of transition metal dissolution, thereby achieving efficient and continuous water removal and inhibiting the dissolution of transition metals. At the same time, the composite diaphragm can reduce the overpotential of lithium metal batteries, protect the SEI membrane from corrosion and damage by acidic substances, and prevent lithium dendrites from piercing the diaphragm, thereby improving battery safety.

[0055] The electrolyte gel includes at least one of PVDF or PVDF-HFP, and the electrolyte gel is used as a binder to improve adhesion of the metal frame material to the base film.

[0056] Step S2, coating the slurry on a base film, and subjecting the slurry to a heating, drying and curing treatment to obtain the composite diaphragm.

[0057] The material of the base membrane is selected from at least one of polyolefin, glass fiber, and polyimide. A conventional commercial diaphragm can be directly selected as the base membrane, and the base membrane is used to improve the mechanical strength of the composite diaphragm.

[0058] The heating, drying and curing treatment comprises: drying in a blast oven at 50° C.-90° C., and then transferring to a vacuum oven and drying at 50° C.-120° C. for more than 12 hours.

[0059] The coating method includes knife coating, gravure roller coating, dip coating, narrow coating or spray coating.

[0060] The slurry coating thickness ranges from 10 to 75 μm.

[0061] In order to improve the water and acid absorption performance of the water and acid absorption membrane, a metal organic framework material with a high specific surface area and polar groups in the pores can be selected. In a specific embodiment, the specific surface area of ​​the metal organic framework material ranges from 700 to 1300 m 2 / g.

[0062] This technical solution can use traditional commercial diaphragms as substrates, commercial electrolyte gels such as PVDF and PVDF-HFP as binders, and select high specific surface areas (700-1300m2) with moderate pore sizes (0.48-0.9nm) and suitable pore environments (oxygen nucleophilic ligands). 2 / g) of stable MOF materials (MO-801, MOF-303, MOF-74, etc.), mixed with MOF materials in a ratio of 50-90%, homogenized and coated, dried, activated and other steps to obtain a composite diaphragm with a thickness of 35-100μm. The method is simple and feasible and can be directly used for industrial large-scale production of new composite diaphragms. The composite diaphragm can effectively and in real time remove the trace water remaining in the electrolyte and the water and Lewis acid impurities (HF, PF 5 ,POF 3 ,HPO 2 F 2 ,H 2 PO 3 F), protect high nickel cathode materials from corrosion, inhibit transition metal dissolution, reduce ion crosstalk problems, and improve battery life and safety. Furthermore, the composite diaphragm can reduce the overpotential of lithium metal batteries and effectively inhibit the growth of lithium dendrites.

[0063] The present invention also provides a method for preparing a MOF composite membrane, comprising the following steps:

[0064] (1) mixing a metal organic framework material and an electrolyte gel in a mass ratio of 5:5 to 9:1 to prepare a slurry;

[0065] (2) The slurry is coated on a base film, and subjected to a heating, drying and curing treatment to obtain the composite diaphragm.

[0066] This technical solution can use traditional commercial membranes as the substrate, commercial electrolyte gels such as PVDF and PVDF-HFP as the binder, and mix MOF materials in a ratio of 50-90%, and obtain a composite membrane with a thickness of 35-100 μm through drying and activation steps. The method is simple and feasible and can be directly used for industrial large-scale production of new composite membranes.

[0067] In order to solve the above problems, an embodiment of the present invention provides a battery, comprising the above-mentioned composite diaphragm.

[0068] Batteries include alkali metal batteries and fuel cells. Alkali metal batteries include lithium ion batteries, sodium ion batteries, magnesium ion batteries, potassium ion batteries and other alkali metal ion batteries. Composite diaphragms can be used not only in lithium ion battery diaphragms, but also in sodium ion battery diaphragms, fuel cell diaphragms, potassium ion batteries, magnesium ion battery diaphragms and other battery systems.

[0069] In a specific embodiment, the alkali metal ion battery is a lithium ion battery, and the positive electrode material of the lithium ion battery can be a nickel-cobalt-manganese ternary material, thereby inhibiting the dissolution of transition metals through a composite diaphragm, reducing ion crosstalk problems, and improving battery life and safety. Of course, in other embodiments, the positive electrode material can also be selected from at least one of lithium manganese oxide, lithium nickel oxide, and lithium-rich layered materials.

[0070] The negative electrode material of the lithium-ion battery can be selected from at least one of graphite, metallic lithium, silicon-carbon, phosphorus-carbon, silicon, and phosphorus.

[0071] The alkali metal ion battery provided by the embodiment of the present invention can absorb trace water in the electrolyte and HF and other Lewis acid impurities generated by the decomposition of lithium salts in real time, effectively inhibit the HF and other acidic impurities from dissolving the transition metals in the high-nickel ternary positive electrode material, reduce the ion crosstalk problem, and improve the battery life and safety.

[0072] The composite diaphragm and its preparation method and the battery of the present invention are further described in detail below in combination with specific examples and comparative examples.

[0073] Example 1

[0074] Preparation of composite diaphragm

[0075] Take ZrOCl 2 8H 2 O 3.22g (10mmol), fumaric acid 1.16g (10mmol), formic acid 15mL, DMF 40mL in a 250mL round-bottom flask; pre-react at 70℃500r / min for 0.5h; solvent thermal reaction at 130℃500r / min for 12h; wash three times with a large amount of methanol and DMF alternately, centrifuge at 3000r / min for 15min; place the product in a watch glass, vacuum dry and activate at 130℃ for 12h, and the mass of the obtained metal organic framework material product (MOF-801) is 2.39g. The BET and pore size distribution test results of the product are as follows: Figure 1A and Figure 1B shown.

[0076] A certain amount of PVDF powder and N-methylpyrrolidone (acetone, DMF, DMAc, etc.) solvent are mixed in a closed device, stirred at room temperature at a speed of 500 r / min for 10 hours, and a 5 wt% PVDF solution is prepared.

[0077] Weigh 0.3g of the above MOF-801 powder and 4g of PVDF (5wt% solution), add a small amount of NMP, grind to obtain a white colloidal slurry. Use commercial polypropylene battery membrane as the substrate for scraping. After scraping, preliminarily dry at 70°C, and then place under vacuum at 70°C to remove the solvent and residual water to obtain a composite membrane with a thickness of 35-100μm, which is recorded as MOF-801@PP membrane.

[0078] The morphology of MOF-801@PP membrane was characterized, and the test results are shown in Figure 1C .

[0079] The adsorption energy & adsorption density calculation and adsorption energy calculation results of MOF-801 for water and HF molecules are as follows Figure 2 shown.

[0080] The MOF-801@PP membrane was subjected to stability experiments and nitrogen adsorption tests.

[0081] Nitrogen adsorption experiment: MOF-801 was soaked in water and electrolyte (1g / 100mL) for 12h, then centrifuged and purified, and washed alternately with DMF and methanol, and then vacuum dried and activated at 130℃ for 12h. Adsorption / desorption test was performed under nitrogen at 77K. The test results are shown in Figure 3 Figure b in the figure. Among them, MOF-801-WATER represents MOF-801 after being immersed in water, MOF-801-ELE represents MOF-801 after being immersed in electrolyte, and FRESH-MOF-801 represents MOF-801 before being immersed.

[0082] The prepared MOF-801 metal organic framework material was immersed in water and electrolyte ((1g / 100mL)) for 7 days, then activated and dried, and XRD test was performed. The test results are shown in Figure 3 .

[0083] Battery Assembly

[0084] NCM622 is used as the positive electrode (active material loading is 5-8 mg / cm 2 ), lithium metal as negative electrode, 1M LiPF with a water content of 317ppm 6 / EC-DMC electrolyte (1M LiPF 6 Ethylene carbonate / dimethyl carbonate (EC / DMC) (3 / 7, v / v) electrolyte with 317 ppm water added) and MOF-801@PP membrane as battery separator were assembled into CR2032 button cells, activated at 0.1C and cycled for 300 times at 0.5C. The test results are shown in Figure 2. Figure 4 The test results of transition metal dissolution in NCM622||Li battery are shown in Figure 5 shown.

[0085] The CR2032 button-type lithium symmetric battery was assembled using lithium metal sheet electrode material and an electrolyte with a water content of 317 ppm. -2 Lithium deposition / stripping experiments were carried out under current density conditions. The test results are shown in Fig.10 .

[0086] Example 2

[0087] The difference between Example 2 and Example 1 is that the mass ratio of MOF-801 powder to PVDF is changed, MOF-801:PVDF=1:1. The remaining operation steps are the same as Example 1.

[0088] NCM622 is used as the positive electrode (active material loading is 5-8 mg / cm 2 ), lithium metal as negative electrode, 1M LiPF with a water content of 317ppm 6 / EC-DMC electrolyte (1M LiPF 6 Ethylene carbonate / dimethyl carbonate (EC / DMC) (3 / 7, v / v) electrolyte with 317 ppm water added), the composite membrane of Example 2 was used as the battery membrane, and CR2032 button cells were assembled, activated at 0.1C, and cycled for a long period at 0.5C. The charge and discharge voltage range was 2.7-4.3V, and the test results are shown in Figure 6 .

[0089] Example 3

[0090] The difference between Example 3 and Example 1 is that the mass ratio of MOF-801 powder to PVDF is changed, MOF-801:PVDF=9:1. The remaining operation steps are the same as Example 1.

[0091] NCM622 is used as the positive electrode (active material loading is 5-8 mg / cm 2 ), lithium metal as negative electrode, 1M LiPF with a water content of 317ppm 6 / EC-DMC electrolyte (1M LiPF 6 Ethylene carbonate / dimethyl carbonate (EC / DMC) (3 / 7, v / v) electrolyte with 317 ppm water added), the composite membrane of Example 3 was used as the battery membrane, and CR2032 button cells were assembled, activated at 0.1C, and cycled for a long period at 0.5C. The charge and discharge voltage range was 2.7-4.3V, and the test results are shown in Figure 6 .

[0092] Example 4

[0093] The difference between Example 4 and Example 1 is that the coating thickness of MOF-801 is changed to obtain a composite membrane with a thickness of 50 μm. The remaining operating steps are the same as those of Example 1.

[0094] NCM622 is used as the positive electrode (active material loading is 5-8 mg / cm 2 ), lithium metal as negative electrode, 1M LiPF with a water content of 317ppm 6 / EC-DMC electrolyte (1M LiPF 6 Ethylene carbonate / dimethyl carbonate (EC / DMC) (3 / 7, v / v) electrolyte with 317 ppm water added), the composite membrane of Example 4 was used as the battery membrane, and CR2032 button cells were assembled, activated at 0.1C, and cycled for a long period at 0.5C. The charge and discharge voltage range was 2.7-4.3V, and the test results are shown in Figure 7 .

[0095] Example 5

[0096] The difference between Example 5 and Example 1 is that the coating thickness of MOF-801 is changed to obtain a composite membrane with a thickness of 100 μm. The remaining operation steps are the same as those of Example 1.

[0097] NCM622 is used as the positive electrode (active material loading is 5-8 mg / cm 2 ), lithium metal as negative electrode, 1M LiPF with a water content of 317ppm 6 / EC-DMC electrolyte (1M LiPF 6 Ethylene carbonate / dimethyl carbonate (EC / DMC) (3 / 7, v / v) electrolyte with 317 ppm water added), the composite membrane of Example 5 was used as the battery membrane, and a CR2032 button battery was assembled, activated at 0.1C, and cycled for a long period at 0.5C. The charge and discharge voltage range was 2.7-4.3V, and the test results are shown in Figure 7 .

[0098] Example 6

[0099] The difference between Example 6 and Example 1 is that the positive electrode material is changed. NCM811 with higher nickel content and greater energy density is used as the positive electrode material, and lithium metal is used as the negative electrode. 1M LiPF with a water content of 317ppm is used. 6 / EC-DMC electrolyte (1M LiPF 6Ethylene carbonate / dimethyl carbonate (EC / DMC) (3 / 7, v / v) electrolyte was added with 317 ppm of water), the MOF-801@PP membrane of Example 1 was used as a battery separator, and a CR2032 button battery was assembled, activated at 0.1C, and cycled for a long period at 0.2C. The charge and discharge voltage range was 2.7-4.3 V. The test results are shown in Figure 8 The test results of transition metal dissolution in NCM811||Li battery are as follows: Fig. 9 shown.

[0100] Comparative Example 1

[0101] NCM622 is used as the positive electrode (active material loading is 5-8 mg / cm 2 ), lithium metal as negative electrode, 1M LiPF with a water content of 317ppm 6 / EC-DMC electrolyte (1M LiPF 6 Ethylene carbonate / dimethyl carbonate (EC / DMC) (3 / 7, v / v) electrolyte with 317ppm water added), commercial polypropylene diaphragm (PP film) was used as the separator, CR2032 button cells were assembled, activated at 0.1C, and cycled for a long period at 0.5C, with a charge and discharge voltage range of 2.7-4.3V. Test results are shown in Figure 4 .

[0102] Comparative Example 2

[0103] NCM811 is used as the positive electrode material, lithium metal is used as the negative electrode, and 1M LiPF with a water content of 317ppm 6 / EC-DMC electrolyte (1M LiPF 6 Ethylene carbonate / dimethyl carbonate (EC / DMC) (3 / 7, v / v) electrolyte was added with 317 ppm of water), the MOF-801@PP membrane of Example 1 was used as the battery separator, and the separator was a commercial polypropylene separator (PP membrane). CR2032 button batteries were assembled, activated at 0.1C, and cycled for a long period at 0.2C. The charge and discharge voltage range was 2.7-4.3 V. The test results are shown in Figure 8 The test results of transition metal dissolution in NCM811||Li battery are as follows: Fig. 9 shown.

[0104] The electron microscope image of the composite diaphragm is shown in Figure 1C As shown. The left picture is the surface morphology, and the right picture is the side morphology. Figure 1C As shown, in the composite membrane prepared using metal organic framework materials, MOF-801 crystal particles are evenly distributed and densely stacked, and the thickness of the composite membrane is about 35μm.

[0105] Among them, MOF-801-Water represents MOF-801 after being immersed in water, MOF-801-ELE represents MOF-801 after being immersed in electrolyte, and MOF-801Fresh represents MOF-801 before being immersed.

[0106] like Figure 3 As shown in Figures 3a and 3b, its XRD diffraction peaks and nitrogen adsorption experimental data show that MOF-801 can maintain complete crystallinity under extreme conditions.

[0107] Figure 4 By comparing the acid and water removal performance and corresponding electrochemical performance of the MOF-801@PP membrane and the commercial PP membrane, and by comparing the specific capacity and coulombic efficiency of Example 1 and Comparative Example 1, it is proved that the MOF-801@PP-based composite membrane has higher stability.

[0108] Figure 8 By comparing the acid and water removal performance and corresponding electrochemical performance of the MOF-801@PP membrane and the commercial PP membrane, and by comparing the specific capacity and coulombic efficiency of Example 6 and Comparative Example 2, it is proved that the composite membrane has higher stability.

[0109] Fig.10 The lithium symmetric battery cycling performance of MOF-801@PP membrane and PP membrane using aqueous electrolyte was compared. Fig.10 Figure a shows that the polarization potential of the PP membrane-based battery dropped suddenly when the cycle reached 438h, indicating that it was short-circuited. However, the MOF-801@PP membrane can effectively reduce the polarization potential. The corresponding polarization potential after 500h of cycling is still maintained at a low level, indicating that the MOF-801 material can effectively improve the lithium ion pathway, improve the lithium ion deposition / stripping effect, and increase the life of the lithium metal battery. Figure bd shows the PP membrane-based lithium symmetric battery at 30mA cm -1 According to the SEM image of the lithium metal surface morphology under the microscope, the SEI layer thickness is as high as 180μm, and the surface is severely powdered, indicating that the dead lithium problem is quite serious. The lithium metal surface of the MOF-801@PP-based lithium symmetric battery presents a dense and smooth microscopic morphology, and the SEI layer thickness is relatively thin (46μm), corresponding to a high lithium ion transmission flux and good deposition and stripping performance.

[0110] It can be seen that the composite diaphragm provided in the embodiment of the present application can effectively and in real time remove the trace water remaining in the electrolyte and the water and Lewis acid impurities (HF, PF 5 ,POF 3 ,HPO 2 F 2 ,H 2 PO 3F), protect high nickel cathode materials from corrosion, inhibit transition metal dissolution, reduce ion crosstalk, and improve battery life and safety. At the same time, the composite diaphragm can reduce the overpotential of lithium metal batteries and effectively inhibit the growth of lithium dendrites.

[0111] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0112] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

[0113] Although the embodiments of the present invention are disclosed above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A composite diaphragm, characterized in that: Prepared by the following method: (1) mixing a metal organic framework material and an electrolyte gel in a mass ratio of 5:5 to 9:1 to prepare a slurry, wherein the pore size range of the metal organic framework material is 0.48-0.9 nm; (2) The slurry is coated on a base film, and subjected to a heating, drying and curing treatment to obtain the composite diaphragm.

2. The composite diaphragm according to claim 1, characterized in that: The heating, drying and curing treatment comprises: drying in a forced air oven at 50-90° C., and then transferring to a vacuum oven and drying at 50-120° C. for more than 12 hours.

3. The composite diaphragm according to claim 1, characterized in that: The coating method includes blade coating, gravure roller coating, dip coating, narrow coating or spray coating, and the slurry coating thickness ranges from 15 to 80 μm.

4. A composite diaphragm, characterized in that: It comprises a base film and a metal organic framework material layer, wherein the metal organic framework material layer is attached to at least one side surface of the base film, the metal organic framework material layer comprises a metal organic framework material, and the pore size range of the metal organic framework material is 0.48-0.9nm.

5. The composite diaphragm according to claim 4, characterized in that: The metal organic framework material layer further includes an electrolyte gel, wherein the electrolyte gel includes at least one of PVDF or PVDF-HFP, and a weight ratio of the metal organic framework material to the electrolyte gel is 5:5 to 9:

1.

6. The composite diaphragm according to any one of claims 1 to 5, characterized in that: The specific surface area of ​​the metal organic framework material is in the range of 700 to 1300 m 2 / g.

7. The composite diaphragm according to any one of claims 1 to 5, characterized in that: The metal organic framework material is selected from at least one of MOF-801, MOF-303, and MOF-74.

8. The composite diaphragm according to any one of claims 1 to 5, characterized in that: The material of the base film is selected from at least one of polyolefin, glass fiber and polyimide.

9. The composite diaphragm according to any one of claims 1 to 5, characterized in that: The thickness of the diaphragm is 35 μm to 100 μm.

10. A battery, characterized in that: Comprising the composite diaphragm as described in any one of claims 1 to 9.